1995
DOI: 10.1159/000244263
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Adaptations at Birth and Neonates Delivered Vaginally and by Cesarean Section

Abstract: In order to assess the possible influence of differences in delivery mode on cardiovascular adaptation at birth, we measured left ventricular output and its regional distribution in the major organs sequentially using an echographic technique during the first 96 h of life. We studied 27 normal newborns, of whom 15 were delivered vaginally and 12 by cesarean section. We also measured umbilical arterial and venous catecholamine concentrations. The umbilical arterial epinephrine and norepinephrine concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…These changes are likely a part of neonatal adaptation after birth. 3,6,[23][24][25][26] As shown in earlier studies, the intracranial and visceral hemodynamics change dramatically after birth, and a severe increase in the BFV and decrease in cerebrovascular resistance take place during the first 5 days of life, with the largest changes occurring within the first 24 hours. 3,5,25 Previous studies have found a significant increase of the cerebral BFV by as early as 12 hours of age.…”
Section: Discussionmentioning
confidence: 55%
“…These changes are likely a part of neonatal adaptation after birth. 3,6,[23][24][25][26] As shown in earlier studies, the intracranial and visceral hemodynamics change dramatically after birth, and a severe increase in the BFV and decrease in cerebrovascular resistance take place during the first 5 days of life, with the largest changes occurring within the first 24 hours. 3,5,25 Previous studies have found a significant increase of the cerebral BFV by as early as 12 hours of age.…”
Section: Discussionmentioning
confidence: 55%
“…The surge is induced by labor, which is why infants delivered vaginally have considerably higher cord artery and/or cord vein levels of norepinephrine (NE), and/or epinephrine (EPI), than those delivered by elective cesarean section [2][3][4][5]. Catecholamines are essential for postnatal adaptation and contribute to the regulation of cardiac output, blood pressure, thermogenesis, surfactant release, lung liquid production and absorption, as well as the regulation of blood glucose levels [6].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma CAs, epinephrine and norepinephrine, play a crucial role at birth in adapting the neonate to extrauterine life by promoting lung maturation, increasing cardiovascular performance, mobilizing glucose, and regulating blood flow to vital organs such as brain (Faxelius et al 1983(Faxelius et al , 1984Sperling et al 1984;Habib et al 1991; Barker and Olver 2002). Several groups have demonstrated that humans born by elective C-section have markedly reduced levels of plasma CAs at birth compared to vaginally born neonates (Irestedt et al 1982;Jones and Greiss 1982;Faxelius et al 1983Faxelius et al , 1984Agata et al 1995;Vogl et al 2006). We and others have previously shown that, similar to findings in humans, plasma CAs at birth are also reduced in rats born by C-section compared to vaginal birth (El-Khodor and Boksa 1997;Ronca et al 2006).…”
Section: Introductionmentioning
confidence: 99%